Exploring the cultural perspectives and implications of infertility among couples in the Talensi and Nabdam Districts of the upper east region of Ghana - Anthony Kolsabilik Kuug; Sindiwe James; Jardien-Baboo Sihaam (BMC, 2023)
Abstract Background Infertility remains a major clinical and social problem, affecting approximately one in every 10 couples. It is a reproductive health condition that is silently experienced with deep repercussions in the essence of self. In Ghana childbearing is considered a social prestige, where the couples are unduly pressurized to bear children for purposes of genealogical continuity. Purpose This study explored the cultural perspectives and implications among males and females experiencing infertility in the Talensi and Nabdam districts of the Upper East Region of Ghana. Methods This study used an ethnographic design to explore the perspectives of couples on socio-cultural beliefs about infertility on 15 participants made up of 8 male and 7 female couple units. Participants were selected using a purposive sampling technique while semi-structured interviews were used to explore the cultural implications on male and female couple units. The data were analysed using Tesch's method of analysing qualitative data. Results Two broad themes and five subthemes emerged from the data analysis regarding the cultural implications of infertility. The major themes and subthemes include: (1) Varying cultural perceptions of infertility (Cultural beliefs and perceptions regarding causes of infertility, cultural consequences of infertility and traditional remedies for infertility), and (2) family dynamics stemming from infertility (abuse from family members, and parenthood as a standard for family inheritance). Conclusions This study adduces evidence of the cultural implications of infertility in rural Ghana. Considering the cultural inclination of most Ghanaian communities, especially the current study setting, it is imperative that policymakers and public health practitioners should consider fertility interventions that are culturally sensitive. Also, culturally sensitive intervention programs that are targeted at increasing the awareness of the rural population on fertility and its treatment should be considered.